2011
DOI: 10.1007/s12272-011-0600-7
|View full text |Cite
|
Sign up to set email alerts
|

Trimebutine as a modulator of gastrointestinal motility

Abstract: Trimebutine has been used for treatment of both hypermotility and hypomotility disorders of the gastrointestinal (GI) tract, such as irritable bowel syndrome. In this issue, Tan et al. (2011) examined the concentration-dependent dual effects of trimebutine on colonic motility in guinea pig. The authors suggested that trimebutine attenuated colonic motility mainly through the inhibition of L-type Ca(2+) channels at higher concentrations, whereas, at lower concentrations, it depolarized membrane potentials by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
12

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 20 publications
0
11
0
12
Order By: Relevance
“…In this regard, P‐317 is similar to a weak and non‐selective opioid agonist, trimebutine. Trimebutine showed no effect on physiological colonic activity but reduced abnormal increase in postprandial motor activity in IBS patients and accelerated slow large bowel transit in constipated patients [27,28]. Therefore, trimebutine is applied in the treatment of both hypermotility and hypomotility disorders of the GI tract, such as IBS‐D and IBS‐C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, P‐317 is similar to a weak and non‐selective opioid agonist, trimebutine. Trimebutine showed no effect on physiological colonic activity but reduced abnormal increase in postprandial motor activity in IBS patients and accelerated slow large bowel transit in constipated patients [27,28]. Therefore, trimebutine is applied in the treatment of both hypermotility and hypomotility disorders of the GI tract, such as IBS‐D and IBS‐C, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Engin et al also reported that TMB incubation decreased KCl‐induced contractions occurred via Ca 2+ influx in rat detrusor smooth muscle strips, suggesting L‐type Ca 2+ channel blocking effect of TMB . Lee et al revealed that TMB can act as Ca 2+ channel blocker at 30–300 μmol/L …”
Section: Discussionmentioning
confidence: 99%
“…Trimebutine maleate (TMB) has been commonly prescribed since 1969 for the treatment of functional gastrointestinal disorders, such as irritable bowel syndrome and dyspepsia . TMB was shown to have spasmolytic activity and the mechanism of its action is complicated.…”
Section: Introductionmentioning
confidence: 99%
“…In overlapping disorders trimebutine could act: as a modulator of gastrointestinal tract motility being a promising candidate for treatment of hypermotility and hypomotility disorders [7]; by hastening gastric emptying, shortening the lag period, causing a premature phase III of the migrating motor complexes in the gut and controlling colonic contractile action [2,8]; by inducing release of gastrointestinal agents such as motilin; by modulating visceral sensitivity; by ameliorating symptoms such as diarrhea and abdominal pain [2,8]; and as a possible antimicrobial agent against bacteria that could trigger post-infectious functional gastrointestinal disorders [9,10], thereby requiring additional relative investigation.…”
mentioning
confidence: 99%